Turbidite Plays of Indonesia: An Overview - Herman Darman (Berita Sedimentologi, 2001)
In the last decade significant advances in geologic understanding and exploration technology in Indonesia continue to reduce the risks associated with exploration and development in turbidite plays. New plays are defined based on recently acquired seismic and well data. Turbidite is becoming a very important play in Sumatra, Kalimantan, Java, and Irian.This paper will give a summary of the latest development on the geological concepts of the deep-water successions in Indonesia based on exploration data.